1982
DOI: 10.1007/bf00896497
|View full text |Cite
|
Sign up to set email alerts
|

The Houston parent—child development center and the primary prevention of behavior problems in young children

Abstract: This study reports the effectiveness of the Houston Parent--Child Development Center (PCDC) program for preventing behavior problems in young children. The PCDC is a 2-year, intensive parent-child education program for children 1-3 and their parents. Low-income Mexican American families were randomly assigned to program or control groups. A follow-up of the program 1-4 years later, when children averaged 5 1/2 years of age, was carried out with 128 mothers who were interviewed about behavior problems of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…Mothers of intervention children also reported lower levels of inattention and hyperactive/impulsive difficulties in their children at follow-up NI-Hutchings et al (2007) NI- Jones et al (2007) I- Fergusson et al (2005b) The mothers of intervention children that received home visitation reported that their children had fewer behavior problems at age 3 years NI- Fergusson et al (2005a) I- Johnson and Breckenridge (1982) Teacher reports at ages 8-11 years old showed reduction in behavior problems. A long-term follow-up of children who had participated in parent training programs in Alabama, Louisiana, and Texas (USA) showed few significant differences in their behavior problems and trouble with the law in late childhood/early adolescence according to both parent and teacher reports (with the exception of the early Texas cohorts) (1987) NI-Johnson (2006) I- Kitzman et al (1997) Fewer mothers of intervention children that received home visitation reported that their children had behavioral problems in the borderline/clinical range at age 6 years.…”
Section: Additional Delinquency/crime Outcomesmentioning
confidence: 93%
See 1 more Smart Citation
“…Mothers of intervention children also reported lower levels of inattention and hyperactive/impulsive difficulties in their children at follow-up NI-Hutchings et al (2007) NI- Jones et al (2007) I- Fergusson et al (2005b) The mothers of intervention children that received home visitation reported that their children had fewer behavior problems at age 3 years NI- Fergusson et al (2005a) I- Johnson and Breckenridge (1982) Teacher reports at ages 8-11 years old showed reduction in behavior problems. A long-term follow-up of children who had participated in parent training programs in Alabama, Louisiana, and Texas (USA) showed few significant differences in their behavior problems and trouble with the law in late childhood/early adolescence according to both parent and teacher reports (with the exception of the early Texas cohorts) (1987) NI-Johnson (2006) I- Kitzman et al (1997) Fewer mothers of intervention children that received home visitation reported that their children had behavioral problems in the borderline/clinical range at age 6 years.…”
Section: Additional Delinquency/crime Outcomesmentioning
confidence: 93%
“…Based on the selection criteria described previously, all of the interventions were randomized controlled experiments. Most of the interventions (n=47) could be broadly classified as parent training programs, although some of these studies might have also included home visits (e.g., Abbott-Shim et al 2003;Johnson and Breckenridge 1982;Schweinhart et al 1993;Songua-Barke et al 2001), whereas eight of the studies were considered to be about home visitation programs as defined by Greenwood (2006) (i.e., the research design by Olds et al 1998, for example) (Butz et al 2001;Cullen 1976;Fergusson et al 2005b;Heinicke et al 2001;Kitzman et al 1997;McCarton et al 1997;Olds et al 2004b;Stone et al 1988). The majority of the studies were considered to be small sample studies, with 37 of the studies being based on samples of fewer than 100 children.…”
Section: Characteristics Of Studies Included In the Meta-analysismentioning
confidence: 99%
“…Others have however employed even more ambitious programs involving several actors (teachers, administrators, mental health professionals and parents) to change the structural and functional aspect of the school (Comer, 1985), or implementing a child development centre as a completely new setting supporting behavioural adjustment in school (Johnson & Breckenridge, 1982).…”
mentioning
confidence: 99%
“…Johnson and Breckenridge (1982) found that pro gram children were less likely to have behavior problems reported by their mothers. Fewer behavior problems in the classroom have also been reported for program children by teachers (Johnson & Walker, 1987).…”
Section: Discussionmentioning
confidence: 94%